2017
DOI: 10.1038/s41598-017-00987-y
|View full text |Cite
|
Sign up to set email alerts
|

Apple pomace improves the quality of pig manure aerobic compost by reducing emissions of NH3 and N2O

Abstract: In this study, the effects of apple pomace (AP) addition (0%, 5%, 10%, and 20% on a dry weight basis, named as control, AP1, AP2, and AP3) and citric acid (CA) addition on nitrogen conservation were investigated during aerobic composting of pig manure. Gaseous emissions of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 38 publications
4
13
1
Order By: Relevance
“…Thereafter, the N 2 O emissions decreased gradually and remained at a low level until the end of composting. This emission trend was also reported in previous studies (Awasthi et al, 2017a; Mao et al, 2017). Mao et al (2017) also observed that N 2 O emissions were mainly emitted in the thermophilic phase when apple pomace was added during composting.…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…Thereafter, the N 2 O emissions decreased gradually and remained at a low level until the end of composting. This emission trend was also reported in previous studies (Awasthi et al, 2017a; Mao et al, 2017). Mao et al (2017) also observed that N 2 O emissions were mainly emitted in the thermophilic phase when apple pomace was added during composting.…”
Section: Resultssupporting
confidence: 91%
“…2b. The initial values of pH in other treatments were significantly lower than in CK (6.29), due to the addition of calcium superphosphate and apple waste (Jiang et al, 2014; Mao et al, 2017). Subsequently, pH increased rapidly with increase in temperature and reached peak values due to the rapid volatilization of NH 4 + , and then decreased because of the formation of low‐molecular‐weight fatty acids and carbon dioxide (CO 2 ) emissions from OM degradation (Bernal et al, 2009), which were similar to most of studies of composting (Jiang et al, 2014; Awasthi et al, 2017b; Zhang et al, 2017).…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations